Analisis Pendampingan Pembuatan Handicraft Berbasis Lingkungan dalam Pengamalan P5 di SDN 3 Demulih - Ni Kadek Ayu Artati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research aims to analyze assistance in making environmentally based handicrafts as part of the implementation of the Pancasila Student Profile Strengthening Program (P5) at SDN 3 Demulih. P5 is designed to build student characters who are creative, care about the environment, and are able to work together. This research uses a qualitative descriptive method, this research evaluates the effectiveness of mentoring in increasing students' creativity and awareness of environmentally friendly lifestyles. The research results show an increase in students' ability to use recycled materials to create useful products as well as increased awareness of environmental issues. This program has also succeeded in strengthening the application of Pancasila values, especially cooperation and social responsibility. Apart from improving practical skills, this activity forms students' character who cares about the environment and is oriented towards sustainability.